Surface reconstruction and charge modulation in BaFe2As2 superconducting film. (6th July 2018) - Kim, S; Yi, S; Oh, M; Jang, B G; Nam, W; Yoo, Y-C; Lee, M; Jeon, H; Zoh, I; Lee, H; Zhang, C; Kim, K H; et al.
Abstract: Whether or not epitaxially grown superconducting films have the same bulk-like superconducting properties is an important concern. We report the structure and the electronic properties of epitaxially grown Ba(Fe1− x Co x )2 As2 films using scanning tunneling microscopy and scanning tunneling spectroscopy (STS). This film showed a different surface structure, R45° reconstruction, from those of as-cleaved surfaces from bulk crystals. The electronic structure of the grown film is different from that in bulk, and it is notable that the film exhibits the same superconducting transport properties. We found that the superconducting gap at the surface is screened at the Ba layer surface in STS measurements, and the charge density wave was observed at the surface in sample in the superconducting state.